CONTRIBUTION TO THE KNOWLEDGE OF CHILEAN PANURGINAE (APOIDEA, ANDRENIDAE) (Acta Entomológica Chilena, 2022)
This paper is intented to: a) describe a new species of Liphanthus lrom the North part of Chile and b)desígnate the type species for the Subgenus Paraimhium that was omitted in the original descriplion.
Keywords: Svsiemalics. Hymenoptera, Andrenidae, Panurginae